Impact of rhythmic hand computation in carnatic classical vocal music education - Darshanan, S. (University of Jaffna, 2012)
Rhythmic hand computation is a widely used visible time maintaining technique in carnatic music. However, a common requirement amongst many existing students for carnatic vocal music is that they are struggling to sing the rhythmically difficult songs while rendering rhythmic hand count. This makes it educational practically difficult to cope with beginners in carnatic vocal music, such as 1st and 2nd years bachelors degree students. This paper proposes a rhythmic mind computation (RMC) technique for time maintaining that initially builds hierarchical song learning from a small effort of the entire students, while the remaining time is saved sequentially and the song adapted constructively. The experimental results indicate that the quality of the singing obtained by this method does not degrade while eliminating the hand computational needs. This new RMC is general, and could be applied to any singing task in carnatic vocal music learning in which the song structured with any rhythmic pattern.
Keywords: Carnatic music; Rhythmic mind computation